From intention to impact : a practical guide to diversity, equity, and inclusion - Lazu, Malia C. (Cambridge, Massachusetts : The MIT Press, 2024)
"A practical guide for companies to engage in racial justice work"-- Waking up to uncomfortable truths -- Evolve or die -- Making antiracism the new normal -- From performative action to business performance -- Finding your company's authentic voice -- Goals alone do not make change - uninformed goals are a reputation risk -- Creating a curious work culture -- It's not them... it's you -- Vendor procurement, building a diverse ecosystems -- Where to from here? "A practical guide for companies to engage in racial justice work"-- Description based on print version record and CIP data provided by publisher; resource not viewed.